The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.5935/abc.20180054
|View full text |Cite
|
Sign up to set email alerts
|

Is Lipid Accumulation Product Associated with an Atherogenic Lipoprotein Profile in Brazilian Subjects?

Abstract: BackgroundLipid accumulation product (LAP), a simple and low-cost tool, is a novel biomarker of central lipid accumulation and represents a potential surrogate marker for atherogenic lipoprotein profile. However, its association with lipoprotein subfractions has not been described in the literature.ObjectiveTo determine whether LAP index could be used as a marker of low- and high-density lipoprotein (LDL and HDL) size in Brazilian individuals.MethodsThis cross-sectional study included patients (n = 351) of bot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
6
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 42 publications
1
6
0
1
Order By: Relevance
“…Previous studies mostly assessed obesity by using body mass index (BMI) and waist circumference (WC), however, obesity not only refers to excessive fat accumulation, but also implies the abnormal distribution of fat, and there are significant differences in morphology and function between subcutaneous adipose tissue (SAT) and visceral adipose tissue (VAT) [ 17 ]. Lipid accumulation product (LAP), as a combination of WC and triglycerides (TG), was proved to be an available indicator that reflects visceral obesity, and it was significant associated with total cholesterol, lipoproteins, and glucose [ 18 , 19 ]. Higher LAP significantly increased the risk of hyperuricemia among Chinese rural population [ 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies mostly assessed obesity by using body mass index (BMI) and waist circumference (WC), however, obesity not only refers to excessive fat accumulation, but also implies the abnormal distribution of fat, and there are significant differences in morphology and function between subcutaneous adipose tissue (SAT) and visceral adipose tissue (VAT) [ 17 ]. Lipid accumulation product (LAP), as a combination of WC and triglycerides (TG), was proved to be an available indicator that reflects visceral obesity, and it was significant associated with total cholesterol, lipoproteins, and glucose [ 18 , 19 ]. Higher LAP significantly increased the risk of hyperuricemia among Chinese rural population [ 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…Pontes [34] conducted that LAP was a better indicator of glucose imbalance and a stronger predictor of DM than BMI. Flavia [35] had confirmed that LAP is sensitive to identify impairment related to glucose metabolism even after correction for drug use. However, in our study, the results showed that the presence or absence of hyperglycemia is insignificantly associated with the LAP.…”
Section: Discussionmentioning
confidence: 96%
“…Some researchers use quartiles as the cut-off value for the analysis, while others use tertiles [ 46 , 47 ]. LAP was strongly linked to the atherogenic profile of lipoprotein subfractions in a Brazilian study [ 48 ]. Additionally, LAP was negatively correlated with HDL-C and positively correlated with TC, glucose, insulin, HOMA-IR, and non-esterified fatty acids values.…”
Section: Discussionmentioning
confidence: 99%